Produksi Karya Teater Pakeliran "BIBI ANU" - I Made, Arta Wiguna; Sudiana, I Ketut; Wicaksandita, I Dewa Ketut (JURNAL DAMAR PEDALANGAN, 2025)
The Pakeliran Theater "Bibi Anu" explores the theme of land uncertainty in Bali caused by ongoing land conversion, highlighting the conflict between tradition and modernization that impacts the cultural identity of the Balinese people. The title "Bibi Anu" carries a profound philosophical meaning, with "Bibi" symbolizing a mother as the guardian of life, and "Anu" reflecting the ambiguity of social changes. This work merges puppetry art and theater, following a creative process consisting of three stages: exploration, improvisation, and formation. Each stage reflects the evolving relationship between humans and the land, from harmony with nature to the crisis triggered by rapid social transformations. The performance is divided into three acts, each with significant meaning. The first act portrays harmony between humans and nature based on the Tri Hita Karana principle, which emphasizes balance between humans, God, and nature. The second act examines the shift in traditional values due to tourism, altering the way of life in Bali. The third act focuses on the emotional crisis resulting from the disconnection between people and the land, leading to feelings of loss and anxiety. This work invites critical reflection on the challenge of preserving tradition amid modernization. "Bibi Anu" fosters dialogue on social and environmental changes in Bali, exploring the complex relationship between humans, culture, and nature in a rapidly changing world.